Analisis Kinerja Pengelolaan Keuangan Daerah Pada Kabupaten Labuhan Batu Utara 2016 – 2020 - Fitria, Fitria; Putra Tampubolon, Gabriel Adi; Aulina, Putri (LPPM Universitas Labuhanbatu, 2022)
This research is to determine the Regional Management Performance of North Labuhan Batu by using the Regional Financial Management performance. This research is a descriptive research through secondary data. Data Analysis by calculating Regional Financial Performance. The results of this study indicate that 1) The performance level of Regional Financial Management in Labura Regency ranges from 44.23% - 72.57%.Â including the Medium category, 2) The effectiveness ratio ranges from 111.63% - 107.84% in general it is very effective. The implications of this research for institutions (Labuhan Batu Utara District Government) as policy makers are expected to increase local revenue by maximizing the potential that exists in the region.